Optimization of Harmony Improvement in Led Lights Using The MQPSO Method: Optimisasi Perbaikan Harmonisa Pada Lampu Led Menggunakan Metode MQPSO - Putra, Bintang Pratama Krisna; Setiawidayat, Sabar; Hunaini, Fachrudin (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2024)
Currently, there are many types of lighting used in the lighting field, one of which is LED lighting. Harmonics is a phenomenon in the electrical system that causes quality disturbances because the current waveform or voltage of the power source is distorted and can cause disturbances in the electrical system. In this research, mathlab was used with the MQPSO method to optimize LED lamp harmonics and reduce the THD value. This method uses a series of LED lighting components to optimize harmonic values. The components that make up the LED light circuit in question are resistors, capacitors and inductors. The optimization results show the best R, L, and C values ​​in the 53rd swarm (particle), and convergence values ​​are achieved in the 17th iteration with a fitness value of 0.5 and an R1 value of 550 Ω, and R2 530 Ω, R3 220 Ω, C1 1.0409 μF, C2 1.0117 μF, C3 1.0221 μF, L1 4.9984 H. The resulting THD and C-RMS values ​​are 1.4901% and 61.674%.